Terms, Definitions, Nomenclature, and Routes of Fluid Administration - Chow, Rosalind S. (Frontiers in Veterinary Science, 2021)
Fluid therapy is commonly administered to veterinary patients to improve hemodynamics, replace deficits and maintain hydration. The gradual expansion of medical knowledge and research in the field has led to a proliferation of terms related to fluid products, fluid delivery and body fluid distribution. Consistency in the definition of these terms is important in order to promote clear and accurate communication in clinical and research settings. This article provides an alphabetical glossary of important terms and common definitions, collated through a review of the human and veterinary literature. It also summarizes the common routes of fluid administration in small and large animal species.